Efektivitas antibakteri ekstrak etanol daun bisbul (Diospyros discolor Willd) terhadap bakteri Propionibacterium acnes - Nanda Nadia; D. Elysa Putri Mambang; M. Pandapotan Nasution; Yayuk Putri Rahayu (Journal of Pharmaceutical and Sciences, 2023)
The bisbul plant (Dyospiros discolor Willd) is a plant whose fruit is often consumed by the public. Bisbul leaves are known to have antibacterial and antifungal activity. The purpose of this study was to determine whether the ethanol extract of bisbul leaves (Diospyros discolor Willd) has antibacterial effectiveness against Propionibacterium acnes bacteria. This research was conducted using experimental methods which included sample collection, macroscopic examination, microscopic examination, simplex preparation, characteristic examination, phytochemical screening, preparation of ethanol extract, and testing of antibacterial effectiveness against Propionibacterium acnes bacteria using the agar diffusion method. The results of the macroscopic examination conducted on the bisbul leaf simplex were brownish-green leaves, flat edges, 5 cm long leaves, 4 cm wide leaves, had a distinctive odor and a slightly bitter taste. The simplex characteristic results obtained water content of 4%, water-soluble essence content of 21%, 23% ethanol-soluble extract content, 4.8% total ash content and 0.3% acid-insoluble ash content. Phytochemical screening of simplex powder and ethanol extract of bisbul leaves showed the presence of alkaloids, tannins, flavonoids, steroids/triterpenoids, saponins and glycosides. The results of the antibacterial effectiveness test of the ethanol extract of bisbul leaves showed that the diameter of the inhibition zone was larger at a concentration of 80%, namely 15.98 mm, compared to concentrations of 70% and 60%, namely 15.43 mm and 14.18 mm. From the results of the study it can be concluded that the ethanol extract of bisbul leaves can provide antibacterial effectiveness against Propionibacterium acnes bacteria.